1990
DOI: 10.1037/0021-843x.99.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Film-induced negative affect triggers overeating in restrained eaters.

Abstract: We tested the effects of film-induced negative affect (i.e., exposure to a frightening film) in 60 women classified as either restrained or unrestrained eaters on the basis of their responses to the Revised Restraint Scale (Herman & Polivy, 1980). Exposure to the frightening film, in contrast to a neutral film, was associated with increases in anxiety, sadness, and anger. High restraint subjects exposed to the frightening film ate more than did equally restrained subjects exposed to a neutral film or low restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
4
5

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 12 publications
5
100
4
5
Order By: Relevance
“…Task-induced depression 15,16 and fear [17][18][19] both increased food intake in restrained eaters while decreasing or not changing the eating of unrestrained participants. This methodology, in which highly palatable snack foods are presented during or immediately after mood induction, has great potential for exploring the antecedents of binge eating.…”
Section: Introductionmentioning
confidence: 99%
“…Task-induced depression 15,16 and fear [17][18][19] both increased food intake in restrained eaters while decreasing or not changing the eating of unrestrained participants. This methodology, in which highly palatable snack foods are presented during or immediately after mood induction, has great potential for exploring the antecedents of binge eating.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is widely assumed that restrained eaters restrict their food intake, results from some experimental studies showed that they ate more after a certain disinhibitor (i.e., the forced consumption of a forbidden food, such as a milkshake [preload] or emotional manipulation), whereas unrestrained eaters showed the opposite pattern and ate less (e.g., Herman & Mack, 1975;Hibscher & Herman, 1977;Polivy, Heatherton, & Herman, 1988;Polivy & Herman, 1999;Schotte, Cools, & McNally, 1990). Thus, restraint may lead to disinhibition because certain conditions can disrupt the restriction in dieters and cause them to relinquish their diet (Herman & Polivy, 1980).…”
mentioning
confidence: 99%
“…Herman and Polivy (1980) have proposed that obese people are more likely to eat in response to external and emotional cues because of their tendency towards dietary restraint, rather than as a result of their obesity per se. This proposal has been supported by laboratory and naturalistic studies demonstrating that negative emotional states such as anxiety (Herman & Polivy, 1975;Polivy, Herman, & McFarlane, 1994) and depressed mood (Baucom & Aiken, 1981;Cooper & Bowskill, 1986;Frost, Goolkasian, & Ely, 1982;Ruderman, 1985;Schotte et al, 1990) induce overeating in restrained eaters but not in unrestrained eaters.…”
Section: Summary Of Antecedents and Immediate Cues Of Nhe And Overeatingmentioning
confidence: 72%
“…According to restraint theory, dieting may be a causal factor in their non-hungry eating, because restricting food often results in a greater susceptibility to eating in response to emotional and external triggers (Herman & Polivy, 1980;Schotte et al, 1990). When people begin to restrain their eating, thoughts of food often become more salient, and therefore they become more sensitive to cues and associations.…”
Section: Participants In the Overweight Rangementioning
confidence: 99%
See 1 more Smart Citation